Smallholder Agricultural Carbon Projects In Ghana - Lee, J. (2012)
Farmer involvement in agriculture climate mitigation is essential if projects are to be sustainable and if we are to ensure projects do not compromise farmer livelihoods and food security for agriculture climate mitigation. Climate mitigation projects that involve smallholder farmers may provide solutions decreasing agriculture’s role in global greenhouse gas (GHG) emissions. This report includes one- page project profiles followed by a more in-depth comparative analysis of the projects. The report highlights the interesting differences and similarities among the different programs in Ghana